2020
DOI: 10.1002/saj2.20142
|View full text |Cite
|
Sign up to set email alerts
|

Residue decomposition and priming of soil organic carbon following different NPK fertilizer histories

Abstract: The effect of mineral fertilizer practices on increasing crop yield has been well studied, but few studies have examined the influence of different long-term subtractive fertilization designs on decomposition of crop residues or influence of soil organic carbon (SOC) levels. To assess the combined effects of the long-term (27 yrs) subtractive fertilizer inputs on SOC mineralization rates, we studied the change in added 13 C-labelled corn stem and leaf residue decomposition and the magnitude of priming effect (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…They concluded that N fertilization decreases SOM decomposition and increases the efficiency of C sequestration in soil through higher portions of un-decomposed crop residues. You et al (2020) assessed the combined effects of the long-term (27 years) subtractive fertilizer inputs on SOC mineralization rates and concluded that crop residue decomposition and SOC is affected by historical N, P, and K fertilization, with long-term complete NPK application resulting in greater SOC content and slower SOC mineralization rates with corn leaf addition. All the data indicated the positive role of N application in soil C retention.…”
Section: Effects Of Wc Size and N Application On C Mineralizationmentioning
confidence: 99%
“…They concluded that N fertilization decreases SOM decomposition and increases the efficiency of C sequestration in soil through higher portions of un-decomposed crop residues. You et al (2020) assessed the combined effects of the long-term (27 years) subtractive fertilizer inputs on SOC mineralization rates and concluded that crop residue decomposition and SOC is affected by historical N, P, and K fertilization, with long-term complete NPK application resulting in greater SOC content and slower SOC mineralization rates with corn leaf addition. All the data indicated the positive role of N application in soil C retention.…”
Section: Effects Of Wc Size and N Application On C Mineralizationmentioning
confidence: 99%
“…Moreover, rotation × N fertilizer interaction affected bacterial richness, evenness, and Shannon indices (Table 5). Many studies have exploited the fact that crop residues along with the application of N fertilizer are capable of boosting soil C and N inputs due primarily to higher organic residue deposition within the field (Adiku et al, 2008;Lupwayi et al, 2018;Verzeaux et al, 2016;You et al, 2020). According to Lupwayi et al (2018), the appropriate application of mineral N fertilizer accompanied with the effective turnover of organic amendments such as cover crops is vital in supporting the diversity of soil microbiota.…”
Section: Slope-specific Agricultural Induced Changes In Soil Abiotic ...mentioning
confidence: 99%
“…Capture of CO 2 was undertaken to assess microbial activity, and therefore priming, response to urine additions (e.g. Lambie et al 2013;Zhang et al 2017;Chen et al 2019;You et al 2020). Following solution application, each core was placed into 2.2 L plastic containers (Sistema, Auckland, New Zealand), with 40 mL of 2 M sodium hydroxide solution to trap CO 2 , sealed, and incubated at 25°C, in the dark, for 21 days (Lambie et al 2013).…”
Section: Co 2 Measurementmentioning
confidence: 99%